2021
DOI: 10.3390/ijerph18020473
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Degeneration in Epilepsy: A Systematic Review

Abstract: Introduction: Cerebellar degeneration has been associated in patients with epilepsy, though the exact pathogenic mechanisms are not understood. The aim of this systematic review was to identify the prevalence of cerebellar degeneration in patients with epilepsy and identify any pathogenic mechanisms. Methodology: A systematic computer-based literature search was conducted using the PubMed database. Data extracted included prevalence, clinical, neuroradiological, and neuropathological characteristics of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 89 publications
(67 reference statements)
2
17
0
Order By: Relevance
“…Hagemann et al 20 found a significant association between cerebellar atrophy and epilepsy with generalized tonic‐clonic seizures. Overall, our study confirms the conclusions drawn by Ibdali et al, 32 in their systematic review, that focal (in the majority temporal lobe) epilepsy, poor seizure control, and phenytoin drug therapy are predictors of cerebellar deterioration in patients with epilepsy.…”
Section: Discussionsupporting
confidence: 92%
“…Hagemann et al 20 found a significant association between cerebellar atrophy and epilepsy with generalized tonic‐clonic seizures. Overall, our study confirms the conclusions drawn by Ibdali et al, 32 in their systematic review, that focal (in the majority temporal lobe) epilepsy, poor seizure control, and phenytoin drug therapy are predictors of cerebellar deterioration in patients with epilepsy.…”
Section: Discussionsupporting
confidence: 92%
“…Firstly, this pattern of cerebellar atrophy may be a consequence of epileptic discharges, as it has been shown in other epileptic conditions, especially chronic temporal lobe epilepsy. 26 , 27 In our study, the influence of recurrent seizures on bilateral cerebellar atrophy is supported by the stronger atrophy observed in chronically affected patients. Of interest, anterior and posterior lobes were oppositely affected in acute and chronic patients, with the anterior lobe being spared in the chronic subsample.…”
Section: Discussionsupporting
confidence: 71%
“…Second, adverse effects of antiseizure medications, particularly phenytoin, may have resulted in bilateral, symmetric cerebellar atrophy. 27 However, only 12 of 57 patients received phenytoin in our cohort. Thus, the influence of this drug on measured atrophy is negligible.…”
Section: Discussionmentioning
confidence: 88%
“…This is because both epilepsy and carbamazepine are known to cause cerebellar degeneration. 16 , 17 In patients with epilepsy treated with carbamazepine, it may be impossible to determine if the cerebellar degeneration is due to one or the other. All NS cases in this study had recurrent seizures and were treated with carbamazepine.…”
Section: Discussionmentioning
confidence: 99%